Refleksija vloge učitelja v čezmejnem prostoru - Baloh, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
Teachers in cross-border regions are constantly exposed to situations which are characterised by a rich linguistic and cultural diversity. The article presents the model of cross-border classrooms which was developed in the project EDUKA2. A special emphasis is paid to the role of teacher as reflective practitioner which presupposes knowledge, skills and personality traits necessary for meeting the challenges of the contemporary classroom. The empirical part presents the results of a study aimed at encouraging teachers to reflect upon their teaching and critically examine which changes they could implement in their work on the basis of the knowledge and experiences gained during the project training activities. The results indicate that the teachers are well aware of the benefits provided by the cross-border territory and are willing to implement changes in their teaching practice.
Keywords: cross-border classrooms; čezmejni razredi; medkulturne kompetence učiteljev; sodobna didaktična izhodišča; teacher as reflective practitioner; teachers' intercultural compe-tences; teaching approaches; učitelj kot reflektivni praktik